Impacto de la aplicación de tres variedades de levaduras (S. cerevisiae, S. pastorianus, S. bayanus) en la producción de cerveza artesanal tipo lager - Benites Fernández, Karen Isabel (2024)
The yeasts S. cerevisiae, S. pastorianus, S. bayanus have a positive impact on the fermentation process, but also provide organoleptic compounds, nutrients and metabolites, which help improve the quality of the product. In reference to the results obtained, the following conclusions are made: The concentration of yeasts in the quality of lager-type craft beer is: S. cerevisiae 0.80 - 1x107 cells/ml, S. pastorianus 0.75-1.5 × 106 cells/mL and S. bayanus 1-1.2 × 106 cells/mL. Among the physical and chemical parameters that influence the propagation and fermentation process of the yeast strains S. cerevisiae, S. pastorianus, S. bayanus in the production of lager-type craft beer are the following: pH, temperature and oxygenation. The ale fermentation temperature is 20 to 25 °C; for lager production, the recommendation is 8 to 10 °C for yeast inoculation; During the process, a gradual decrease of 1 °C per day is recommended until reaching 4 °C, decreasing to 1 °C every 8 hours. The pH of wort and beer is especially important during germination and fermentation. Most lager beer yeasts grow optimally at a pH value between 4.0 and 5.0. Oxygenation or agitation of the must during fermentation is an essential prior step during the first hours of the process; The quality of the product will fundamentally depend on this adequate aeration or oxygenation of the must.